OP0063 Impact of baseline interferon pathway activation on widespread gene expression changes with disease flare in lupus patients: Interim report from the bold (biomarkers of lupus disease) study. (23rd January 2014) - Seyhan, A.; O'Toole, M.; Zhang, Y.; Immermann, F.W.; Hill, A.; Reddy, P.; Masferrer, J.; Zhou, T.; Mounts, W.; Whitley, M.; Walker, T.; Kamp, S.; et al.
Abstract : Background: Heterogeneity of clinical manifestations and underlying biology has confounded treatment development and optimal care of systemic lupus erythematosus (SLE) patients. About half of adult SLE patients tend to have stable, high expression levels of genes in the interferon (IFN) signaling pathways. We and others have previously reported differences in expression levels between IFN groups of genes in pathways other than IFN signaling pathways 1, 2, 3, 4, 5 . Objectives: To determine how gene expression changes with disease flare in SLE patients with high versus low expression of IFN pathway genes. Methods: The BOLD study enrolls patients with active disease who are withdrawn from potentially confounding background immunosuppressive therapy and given brief intramuscular steroids (depomedrol) to induce improvement (Improving Visit), and followed until flare (Flare Visit). An interim analysis was conducted by TaqMan® RT-PCR on 23 patients who completed the study. Expression levels of 272 genes (selected based on reported associations with lupus and/or inflammation) were compared between Improving Visit and Flare Visit. Results: Striking expression differences between Improving Visit and Flare Visit were observed for some genes, predominantly associated with the IFN High Group. Expression of most (76%) genes tested did not change with flare (p>0.1). IFN groups did not differ in demographic features. There was a trend towards higher disease activity (CLASI score, p=0.06, BILAG scores p=0.1) at baseline in the IFN high group. Conclusions: This interim report suggests biomarkers in several pathways might be tested as sensitive indicators to guide patient selection and dosing in the development of treatments which affect the TLR/IFN pathway, and to optimize the eventual use of these agents in clinic. Given the heterogeneity of patients with SLE it could be that some of these downstream indicators could help differentiate between patients who are or are not intrinsically good candidates for targeting of IFN signaling pathways. References: O'Toole et al., ACR 2011, Abstract 1407. Baechler et al., PNAS 2003. Bennett et al., J. Exp. Med 2003. Kirou et al., Arthritis and Rheumatism 2005. Petri et al, Lupus 2009. Disclosure of Interest: A. Seyhan Employee of: Pfizer, M. O'Toole Employee of: Pfizer, Y. Zhang Employee of: Pfizer, F. Immermann Employee of: Pfizer, A. Hill Employee of: Pfizer, P. Reddy Employee of: Pfizer, J. Masferrer Employee of: Pfizer, T. Zhou Employee of: Pfizer, W. Mounts Employee of: Pfizer, M. Whitley Employee of: Pfizer, T. Walker Employee of: Pfizer, S. Kamp: None Declared, J. James: None Declared, S. Sridharan Employee of: Pfizer, J. Merrill: None Declared, M. Honczarenko Employee of: Pfizer